Variants in the SNCA Locus Are Associated With the Progression of Parkinson's Disease - Luo, Ningdi; Li, Yuanyuan; Niu, Mengyue; Zhou, Liche; Yao, Mengsha; Zhu, Lin; Ye, Guanyu; Kang, Wenyan; Liu, Jun (Frontiers in Aging Neuroscience, 2019)
Background: Genetic factors have a well-known influence on Parkinson disease (PD) susceptibility, however, no previous studies have investigated the inﬂuence of SNCA mutations on the natural history of Parkinson’s disease using prospective follow-up study. The aim of this study was to assess the risk factors of variation of SNCA on the prognosis symptoms of PD patients. Methods: Fifty PD patients were recruited with 38 v-PSG confirmed PD+RBD patients, and the median follow-up period was 30 months. All patients underwent a comprehensive clinical evaluation at baseline and follow-up, and six SNPs of SNCA (rs356165, rs3857053, rs1045722, rs894278, rs356186, and rs356219) were analyzed. Cox proportional hazards regression models and Kaplan-Meier plot analysis were used to assess the associations between the SNCA variation and the primary and secondary progression outcomes. Results: Based on the clinical assessment, we found that hyposmia was substantially easier to aggravate. Regression analysis showed that patients with T allele of rs1045722 and G allele of rs356219 presented a 34% and 20% decreased risk of progression to the H-Y stage respectively (p=0.022; p=0.005). While for rs894278, G allele-patients showed a 47% decreased risk of olfactory dysfunction (p=0.029). Further subgroup analysis showed that PD+RBD patients with rs356219/G exhibited a 30% and 20% decreased risk of progression on the H-Y stage and MOCA score (p=0.038; p=0.045). Conclusions: Our results indicated that genetic variation in SNCA may contribute to variability natural progression of PD and could possibly be used as a prognostic marker.